DETERMINAÇÃO DO PARAQUAT SOBRE ELETRODOS DE CARBONO VÍTREO MODIFICADO COM FTALOCIANINA TETRASSULFONADA DE NIQUEL EM FILME DE POLI-L-LISINA - Mendes, Cristiane Arcângela de Souza (2007)
This work present an evaluation of a modified glassy carbon electrode with NiTSPc immobilized with film PLL of the determination of paraquat by differential pulse voltammetry. The film was formed applying 20μL of a solution prepared for the mixture of equal volume of NiTSPc 0,8mM and poly-L-lisine (PLL) 0,12mM. The maximum signal to noice ratio was obtained using a 0,1M Britton-Robinson buffer at pH=7,0 as supporting electrolyte.. The electrode modified with NiTSPc/PLL presented PQ reduction currents more accented and voltammetrics profiles better with respect to the electrodes unmodified and modified with CuTSPc/PLL. The best conditions of analyze had been amplitude of pulse 125mV, width of pulse 25mV, speed of sweepings 10mV/s. The maximum relation signal noise was gotten in drain plug Britton-Robinson 0,1M, with pH 7,0 as electrolyte has supported. This sensor presented two reversible peaks for reduction of the PQ around - 0.71 V (peak 1) and - 1,10 V (peak 2) versus E.C S. In these conditions, the modified electrode obtained a linear response range from 1,00 x 10-6 to 1,00 x 10-5 mol L-1 with detection and quantification limits equals to 7,58 x 10-8 mol L-1 (19,5 μg L-1) and 2,5 x 10-7 mol L-1 (64 μg L-1), respectively. The studied sensor presented values below 5%, in terms of relative standard deviation, for repeatability (2,52% for N = 10) and reproducibility (2,97% for N = 5) studies. The recovery in real samples was of 98%.